Experimental Verification of the main MPPT techniques for photovoltaic system - Mohamed Amine Abdourraziq; Mohamed Maaroufi (Institute of Advanced Engineering and Science, 2017)
Photovoltaic (PV) technology is one of the important renewable energy resources as it is pollution free and clean. PV systems have a high cost of energy and low eciency, consequently, they not made it fully attractive as an alternative option for electricity users. It is essential that PV systems are operated to extract the maximum possible power at all times. Maximum Power Point (MPP) changes with atmospheric conditions (radiation and temperature), it is dicult to sustain MPP at all atmospheric levels. Many Maximum Power Point Tracking (MPPT) have been developed and implemented. These methods varied according to several aspects such as a number of sensors used, complexity, accuracy, speed, ease of hardware implementation, cost and tracking eciency. The MPPT techniques presented in the literature indicate that Variable step size of Perturb & Observe (VP&O), Variable step size of Incremental Conductance (VINC) and Perturb & Observe (P&O) using Fuzzy Logic Controller (FLC) can achieve reliable global MPPT with low cost and complexity and be easily adapted to dierent PV systems. In this paper, we established theoretical and experimental verication of the main MPPT controllers (VP&O, VINC, and P&O using FLC MPPT algorithms) that most cited in the literature. The three MPPT controller has been tested by MATLAB/Simulink to analyze each technique under dierent atmospheric conditions. The experimental results show that the performance of VINC and P&O using FLC is better than VP&O in term of response time.